Rethinking working mothers in Singapore : empowerment in the family. - Chang, Adeline. (2013)
Twenty-four years had passed since Arlie Hochschild and Anne Machung published their book, “The Second Shift: Working Parents and the Revolution at Home” in 1989. This classical work has contributed much towards the rich literature on dual-career families, and offered interesting insights into the lives of these families, and especially, the role of women in this “stalled revolution”. Twenty-four years later, working mothers in Singapore still encounter a similar paradox to the women Hochschild interviewed as they attempt to reconcile work and family life. The main puzzle that fuels this research is the question regarding how gender ideologies of the Singaporean working mothers impact upon the meanings they place on the division of labour in the family and subsequently their sense of personal empowerment. This research uses a sample of ten middle class Singaporean working mothers to investigate the relationship between gender ideologies and empowerment. This research argues that empowerment should not be generalized for all women and should instead be examined together with gender ideologies.